A SCORING ALGORITHM FOR DIFFERENTIATED SELECTION OF THE ENDOVIDEOSURGICAL HERNIOPLASTY METHOD IN INGUINAL HERNIAS (Global Conference on Medical and Health Sciences, 2026)
The choice of endovideosurgical technique for inguinal hernia repair is still largely empirical, and recurrence and chronic postoperative inguinal pain have not decreased substantially. An objective, quantitative tool linking method selection to the state of the muscular-aponeurotic frame and to other risk factors is therefore needed.